FIRE PROTECTION PROPERTIES OF MULTI-COMPONENT POLYMER PAINT BASED ON POLYMER FILLER-ALKIDE PAINT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The research work presents the results of research on the production of fire and heat-resistant paints and varnishes based on alkyd paint. It is shown that the resulting compositions have effective fire and heat protection properties.